Research on the Threshold Effect of Digital Transformation on Corporate Performance in Manufacturing Enterprises - Tian , Xinyang (International Journal of Multidisciplinary Research, 2025)
In the digital economy era, as a pillar of China's economy, the manufacturing sector must pursue digital transformation, which is crucial to high-quality development and modernization goals. Using Shanghai and Shenzhen A-share manufacturing enterprises from 2015 to 2023 as samples, this paper explores the threshold effect of digital transformation on corporate performance, analyzes heterogeneity, relevant moderating and mediating roles, and provides suggestions for enterprises' transformation.